An Analysis of some Socio-economic Implications Influencing People’s Participation in Silvi-pastoral Systems of a Micro Watershed In Garhwal Himalaya - Singhal, R. M.; Kumar, Vinay (Indian Forester, 1997)
A study based on questionnaire was conducted from August to December 1994 with the objective of analyzing some of the socio-economic implications influencing people’s participation in silvipastoral activities in the villages of Pidligad Micro Watershed ofGarhwal Himalaya. Statistical tests revealed that farm size, household size, total number of animals in the household and distance travelled in fuelwood collection were statistically significant at 95% level. Number of days used for fodder collection was not statistically significant. The study recommends that detailed analysis of the clientele sliould be prerequisite in any silvi-pastoral activities to be undertaken.